Design and Synthesis of Tunable Chiral 2, 2′‐Bipyridine Ligands: Application to the Enantioselective Nickel‐Catalyzed Reductive Arylation of Aldehydes. (26th February 2022) - Zhang, Shuai; Perveen, Saima; Ouyang, Yizhao; Xu, Liang; Yu, Tao; Zhao, Min; Wang, Linghua; Song, Peidong; Li, Pengfei
Abstract: A new class of chiral 2, 2′‐bipyridine ligands, SBpy, featuring minimized short‐range steric hindrance and structural tunability was rationally designed and developed, and the effectiveness was demonstrated in the first highly enantioselective Ni‐catalyzed addition of aryl halides to aldehydes. In comparison with known approaches using preformed aryl metallic reagents, this reaction is more step‐economical and functional group tolerant. The reaction mechanism and a model of stereocontrol were proposed based on experimental and computational results. Abstract : A tunable chiral 2, 2′‐bipyridine scaffold SBpy was rationally designed and enabled a general and highly enantioselective Ni‐catalyzed addition of aryl halides to aldehydes. This approach is more step‐economic than conventional strategies and allowed the preparation of various diaryl carbinols without the need to use preformed metallic reagents.